Setting of import tolerances for lufenuron in various commodities of plant and animal origin. (18th August 2020) - ; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Crop Protection AG submitted a request to the competent national authority in Portugal to set import tolerances for the active substance lufenuron in grapefruits, oranges, limes, pome fruits, peppers, coffee, sugar canes, muscle, fat, liver and kidney on the basis of the authorised uses of lufenuron in Brazil, Chile and Morocco. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for all commodities under assessment. For oranges, limes, pome fruits, peppers and coffee beans and commodities of animal origin, the submitted data indicated no need to modify the existing EU MRLs. For grapefruits and sugar cane, the residue data indicated that higher MRLs would be needed. Adequate analytical methods for enforcement are available to control the residues of lufenuron in plant and animal matrices. Based on the risk assessment results, EFSA concluded that the existing EU uses and the authorised uses of lufenuron in Brazil, Chile and Morocco will not result in chronic consumer exposure exceeding the toxicological reference value. Considering, however, that the estimated exposure is close to the acceptable daily intake (ADI) and in the light of the expiry of the approval of the active substance, EFSA recommends the review of the existing MRLs taking into account that the MRLs based on the EU uses will become obsolete.